Pengaruh Kepemimpinan Kepala Sekolah Terhadap Motivasi Kerja Guru di SMP Negeri 1 Kota Pematangsiantar - Nurmaliyah Pardede (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2021)
In an effort to improve the quality and quality of education, teacher performance is the main target. Furthermore,there needs to be   serious  and  deep attention to improving teacher performance from various related parties such as principals, school stakeholders,   supervisors,and the Minister of Education andCulture. Theperformance of the teacher can be influenced by several factors, one of which is the leadership of the Principal. If the better and conducive the leadership of a Principal, the better the motivation of the work of teachers who are in the scope of the School and its leadership. This research was conducted to find out how much influence the leadership of the principal has on the motivation of teachers at SMPN 1 Pematangsiantar city. The method used in this study is a qualitative method. The results of the study, are: 1. The leadership of the principal greatly affects the performance of teachers. Which means that the more conducive the leadership presented by the principal, the better the performance of the teachers. 2. A teacher's work motivation can also affect how high he or she performs. Which means that the better and higher the motivation of the teacher's work to carry out his duties and responsibilities, the better the performance he does. 3. There is also a significant influence between the leadership of the principal with work motivation that equally affects and can improve teacher performance. Therefore, the better the leadership of the principal and work motivation, the higher the performance of the teacher.